2022
DOI: 10.1016/j.esxm.2022.100529
|View full text |Cite
|
Sign up to set email alerts
|

The AdVance Sling and Male Sexual Function: A Prospective Analysis on the Impact of Pelvic Mesh on Erectile and Orgasmic Domains in Sexually Active Men With Postprostatectomy Stress Urinary Incontinence

Abstract: Background Transvaginal pelvic mesh surgery has been shown to cause female sexual dysfunction. Aim To evaluate the sexual function impact of AdVance male sling (MS) on erectile and orgasmic domains. Methods A review of a prospectively collected database was conducted in all sexually active men who underwent AdVance MS for postprostatectomy stress urinary inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…22,[29][30][31][32][33][34][35] More recently, one study reported that the AdVance male sling appears to improve male sexual function with regards to erectile and orgasm domains in addition to urinary continence. 36 Reported adverse events are generally mild with transient urinary retention and groyne pain being the most frequently encountered, and the need for explantation is exceedingly low. 37 Patients with severe incontinence (>400 g/24-h pad weight), a history of prior radiotherapy or coexisting storage dysfunction are more likely to have poorer outcomes.…”
Section: Advance Sling (Boston Scientific Formerly American Medical S...mentioning
confidence: 99%
See 1 more Smart Citation
“…22,[29][30][31][32][33][34][35] More recently, one study reported that the AdVance male sling appears to improve male sexual function with regards to erectile and orgasm domains in addition to urinary continence. 36 Reported adverse events are generally mild with transient urinary retention and groyne pain being the most frequently encountered, and the need for explantation is exceedingly low. 37 Patients with severe incontinence (>400 g/24-h pad weight), a history of prior radiotherapy or coexisting storage dysfunction are more likely to have poorer outcomes.…”
Section: Advance Sling (Boston Scientific Formerly American Medical S...mentioning
confidence: 99%
“… 22 , 29 35 More recently, one study reported that the AdVance male sling appears to improve male sexual function with regards to erectile and orgasm domains in addition to urinary continence. 36 …”
Section: Clinical Findingsmentioning
confidence: 99%
“…Despite excellent disease-specific survival, RP often causes debilitating consequences to continence and erectile function. Urinary incontinence is common after RP, occurring in 2% to 87% of patients ( 4 , 5 ). While continence improves in most men over time, this recovery time is variable with some patients requiring up to 12 months ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%